2013
DOI: 10.1088/1478-3975/10/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

Follow-the-leader cell migration requires biased cell–cell contact and local microenvironmental signals

Abstract: Directed cell migration often involves at least two types of cell motility that include multicellular streaming and chain migration. However, what is unclear is how cell contact dynamics and the distinct microenvironments through which cells travel influence the selection of one migratory mode or the other. The embryonic and highly invasive neural crest (NC) are an excellent model system to study this question since NC cells have been observed in vivo to display both of these types of cell motility. Here, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
3
32
1
Order By: Relevance
“…The size of the migratory collective depends on its position along the body axis: while in the head the cranial NC (CNC) forms larger collectively moving groups, in the trunk the streams can be as thin as a single cell and perform chain migration. 13 The migration of the trunk NC has been suggested to be driven by a leader cell, similar to what has been shown in angiogenic sprouting. 14 Here we focus on the CNC where this distinction of leader-follower cells is less clear and therefore which can be considered more of an emergent migratory property of this mesenchymal cell group.…”
Section: The Migrating Neural Crestmentioning
confidence: 66%
“…The size of the migratory collective depends on its position along the body axis: while in the head the cranial NC (CNC) forms larger collectively moving groups, in the trunk the streams can be as thin as a single cell and perform chain migration. 13 The migration of the trunk NC has been suggested to be driven by a leader cell, similar to what has been shown in angiogenic sprouting. 14 Here we focus on the CNC where this distinction of leader-follower cells is less clear and therefore which can be considered more of an emergent migratory property of this mesenchymal cell group.…”
Section: The Migrating Neural Crestmentioning
confidence: 66%
“…As cranial NCCs migrate along the rhombomeres, subpopulations migrate into and populate some of the branchial arches (Kuo and Erickson, 2010). The NCCs of the hyoid stream traverse over rhombomere 4 in a wide, densely packed stream, while those of the branchial stream migrate over rhombomere 7 in narrow, linear chain-like arrays (Wynn et al, 2013). Although these cells have different migratory characteristics, NCCs swapped between rhombomeres 4 and 7 in chick are able to adopt the local migratory style (Wynn et al, 2013).…”
Section: Migratory Mechanisms and Communicationmentioning
confidence: 99%
“…The NCCs of the hyoid stream traverse over rhombomere 4 in a wide, densely packed stream, while those of the branchial stream migrate over rhombomere 7 in narrow, linear chain-like arrays (Wynn et al, 2013). Although these cells have different migratory characteristics, NCCs swapped between rhombomeres 4 and 7 in chick are able to adopt the local migratory style (Wynn et al, 2013). It is intriguing to consider what mechanisms are at play to enable the transplanted NCCs to adapt to their new microenvironments and take on local migratory patterns.…”
Section: Migratory Mechanisms and Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, electroporation and transgenesis techniques have emerged for labeling populations of neural crest cells with fluorescent tags like GFP or Red Fluorescent Protein (RFP) (Nie et al, 2011; Theveneau et al, 2010); RFP and fluorescent dextrans (Gross and Hanken, 2004) that have made possible high resolution confocal imaging (Kulesa et al, 2013; McKinney et al, 2013). These techniques have made it possible to study cell biological aspects of neural crest migration in many species, enabling the identification of ‘leaders’ and ‘followers’ and neural crest cell-cell interactions (Wynn et al, 2013) and examination of the developmental potential of neural crest cells at different times of exit from the neural tube (McKinney et al, 2013). Because these techniques unilaterally label the neural tube, they have revealed that contralaterally migrating neural crest cells are a major source of progenitor cells for the pain- and temperature-sensing afferents of the dorsal root ganglia (George et al, 2007).…”
Section: Approaches For Examining Migratory Pathways In the Developinmentioning
confidence: 99%